Degradation of Phenol in Aqueous Solution by Advanced Oxidation Process - Jamshidi, Naser; Torabian, Ali; Azimi, Aliakbar; Ghadimkhani, Aliasghar (Asian Journal of Chemistry, 2010)
Advanced oxidation processes (UV, UV/H2O2, UV/H2O2/ Fe(II) and UV/H2O2/Fe(III)) were investigated in lab-scale experiments for degradation of phenol in aqueous solution. The study shows that the Photo-Fenton process, (a mixture of hydrogen peroxide and ferrous or ferric ion), was the most effective treatment process under acidic conditions and produced a higher rate of degradation of phenol at a very short radiation time. It accelerates the oxidation rate by 5-8 times the rate of the UV/H2O2 process. The reaction was influenced by pH, the input concentration of H2O2 and the amount of the iron catalyst and the type of iron salt. The experimental results show that the optimum conditions were obtained at a pH value of 3, with 6 mmol/L H2O2 and 0.5 mmol/L Fe(II) for the UV/ H2O2/Fe(II) system and 6 mmol/L H2O2 and, 0.4 mmol/L Fe(III) for the UV/H2O2/Fe(III) system. As for the UV processes, UV/H2O2/Fe(III) showed the highest degradation rate.